Effects of a glucagon-like peptide-1 analog on appetitive and consummatory behavior for rewarding and aversive gustatory stimuli in rats - Douton, Joaquin E. (Physiol Behav, 2020)
Glucagon-like peptide-1 (GLP-1) is an incretin hormone that is essential for the regulation of food intake and approved for the treatment of type 2 diabetes mellitus and obesity in humans. More recently, GLP-1 has been investigated for its ability to modulate motivation for food and drugs. Reward behavior can be divided into two components: ‘motivational’ (i.e., approach and consummatory behaviors) and ‘affective’ (i.e., perceived palatability). Studies show that GLP-1 analogs reduce the motivation to approach and consume palatable food, but the impact on affective responding is unknown. Thus, the present study tested the effect of the GLP-1 analog, Exendin-4 (Ex-4), on the appetitive response to intraorally delivered sucrose and quinine. Results showed that Ex-4 (2.4ug/kg ip) failed to alter passive drip, appetitive reactions (i.e., mouth movements, tongue protrusions, and lateral tongue protrusions) or aversive reactions (i.e., gapes) to sucrose. Paw-licking, however, was significantly reduced by Ex-4. Treatment with Ex-4 also failed to influence passive drip to quinine, but increased the latency to gape and reduced the total number of gapes emitted. In addition, Ex-4 reduced intake of quinine in water restricted rats, but did not reduce conditioned aversion (i.e., gapes) or avoidance (i.e., reduced intake) of a LiCl-paired saccharin cue. Thus, while Ex-4 had no effect on a learned aversion, it reduced approach and ingestion of sweet and bitter solutions, while leaving the appetitive affective response to the sweet almost intact, and the aversive affective response to the bitter reduced. Treatment with Ex-4, then, differentially modulates appetitive and consummatory components of reward, depending on the valence of the stimulus and whether its valence is learned or innate.